2020
DOI: 10.18517/ijaseit.10.1.10276
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Vulnerability Mapping to Support Spatial Plans in Lhokseumawe City Area

Abstract: Earthquake loads that work on building structures can be determined by doing calculations ground motion on the surface. The amplitude from ground vibration is correlated with earthquake energy and ground solidity (compaction). The ductile ground will amplify the earthquake energy so that it produces strong vibration to the ground and building on the surface. This study will provide a mapping of areas susceptible to seismic vibrations to produce sustainable Lhokseumawe City spatial management plan policies as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Amplification can be interpreted as an amplification of waves from the bedrock to the soil surface due to the differences in the shear wave velocity Vs [37]. According to Tanjung [38], the amplification of earthquake waves can occur when a wave propagates to the ground surface where the dominant frequency of the land has the same frequency as the frequency of the incoming earthquake.…”
Section: Analysis Of Microtremor Datamentioning
confidence: 99%
“…Amplification can be interpreted as an amplification of waves from the bedrock to the soil surface due to the differences in the shear wave velocity Vs [37]. According to Tanjung [38], the amplification of earthquake waves can occur when a wave propagates to the ground surface where the dominant frequency of the land has the same frequency as the frequency of the incoming earthquake.…”
Section: Analysis Of Microtremor Datamentioning
confidence: 99%
“…The map of the distribution of seismic vulnerability values in Lhokseumawe City is shown in (Figure 2). The results of the analysis of seismic vulnerability index values in previous studies showed that Lhokseumawe City and its surroundings had a seismic vulnerability index value of around 0.41 to 18.3 [7]. The Sumatran fault is distributed along the island of Sumatra from Lampung to Andaman Island with a length of more than 1900 km and is divided into several segments [8].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Susceptibility to vibration is not only felt through earthquakes but also by small vibrations called microtremors (Siska et al, 2020). Microtremor is a low-amplitude vibration (0.1 micron -1 micron for the amplitude displacement 0.001 cm/s -0.01 cm/s for the amplitude velocity) that comes from natural or man-made phenomena, such as wind, ocean waves, or vibrations from vehicles that can describe geological conditions near the surface (Haerudin et al, 2020;Kafadar, 2020;Nelson, 2019;Susilo & Wiyono, 2012).…”
Section: Introductionmentioning
confidence: 99%